Fungal diversity and its contribution to the biodeterioration of mural paintings in two 1700-year-old tombs of China. (August 2020) - Ma, Wenxia; Wu, Fasi; Tian, Tian; He, Dongpeng; Zhang, Qi; Gu, Ji-Dong; Duan, Yulong; Ma, Dongxu; Wang, Wanfu; Feng, Huyuan
Abstract: Two subterranean ancient Chinese tombs of over 1700 years old, one from the Jin Dynasty and another from the Han Dynasty, were investigated in relation to black spots associated with microbiological deterioration of brick mural paintings within. The objectives of this study were to characterize the diversity of culturable fungal communities and assess the biodeteriorative potential of the isolated fungi. Culture-dependent methods using four different types of media were used for fungal isolation and specialized agar plates were used for biodeteriorative analyses by monitoring calcite dissolution, proteolytic activity, pH change, and biomineralization capabilities the isolated strains. Physical characterization of the mural samples and biomineralization were carried out using scanning electron microscopy combined with energy dispersive and X-ray diffraction analyses, while fungal acid production was analysed using High-performance liquid Chromatography (HPLC). Results showed that most of the 22 fungal strains isolated belonged to the Penicillium and Aspergillus genera. Differences in fungal community diversity between the two tombs may be attributed to variations in their interior temperature and relative humidity, however the history and drawing techniques used could also be contributing factors. Penicillium aurantiogriseum, Aspergillus versicolor and Penicillium olsonii were found in both tombs, representing the core microflora found in the black spots, thus these three fungi may be the sources of the black spots. More than 68% of the isolated fungi showed proteolytic activity and 27% of the strains produced acids, leading to dissolution of calcium carbonate and decreased pH value. Among the isolates, 5 out of 6 acid-forming fungal strains could also promote biomineralization. Penicillium was the main genus found to form acid and promote biomineralization. These fungi with biodeterioration and biomineralization characteristics were abundant in the black spots, indicating that formation of black spots was relevant to their presence and activity. These results suggest that thriving fungi, primarily driven by the local microenvironment, pose a high risk to brick wall paintings. Highlights: Filamentous fungi contribute to the formation of black spots on mural paintings. The decay of mural paintings through proteolysis, carbonate dissolution, acid production, and biomineralization. The formation of black spots on mural is influenced by the surrounding microenvironmental conditions. Using different methods in tandem should be a prerequisite for the precise assessment of fungal threats to mural paintings.